Genre, Authorship and Contemporary Women Filmmakers - Paszkiewicz, Katarzyna (Edinburgh University Press, 2008)
Examining the significance of women's work in popular film genres, Genre, Authorship and Contemporary Women Filmmakers sheds light on women's contribution to genre cinema through an exploration of filmmakers like Kathryn Bigelow, Diablo Cody, Sofia Coppola and Kelly Reichard. Exploring genres as diverse as horror, the war movie, the Western, the costume biopic and the romantic comedy, the book interrogates questions of authorial subversion, gendered concepts of film authorship and male/female genre divisions, as well as re-evaluating certain genres as a space worthy of feminist criticism. By offering an analysis of the films themselves and the circumstances of production and reception, this book redefines political, theoretical and commercial conceptualisations of women's cinema, and offers new perspectives on how women filmmakers explore the aesthetic and imaginative power of genre.